Iohexol Degradation by Biogenic Palladium Nanoparticles Hosted in Anaerobic Granular Sludge - Quan, Xiangchun; Zhang, Xin; Sun, Yue; Zhao, Jinbo (Frontiers in Microbiology, 2018)
To improve the degradation ability of anaerobic granular sludge (AGS) towards the iodinated contrast media iohexol, biogenic nanoscale palladium (Pd) was formed in AGS via microbial reduction. The Pd hosted in AGS (Pd-AGS) was used for iohexol degradation. The effects of the electron donor, reaction medium, iodide ion fouling, and polymer embedding of the Pd-AGS on the reactivity were investigated. Our results showed the Pd-AGS increased the degradation rate of iohexol, with a conversion rate constant increased by 86.3 folds compared to the AGS control. Various organic compounds were investigated as electron donors to initiate the catalytic activity of Pd-AGS and the promotion achieved with the tested electron donors was in the following order: formate > lactate > ethanol > glucose > acetate. The Pd-AGS had high reactivity in deionized water at mild pH, and almost no reactivity under acidic (pH = 1.2) and alkaline (pH > 11) conditions. The presence of iodide ions in the medium inhibited the catalytic activity of Pd-AGS towards iohexol because of catalyst fouling. Embedding the Pd-AGS in alginate, chitosan, or polyvinyl alcohol could prevent Pd loss but it also retarded the iohexol degradation rate. The Pd-AGS, as a combination of Pd catalyst and AGS, provides a novel strategy for iohexol degradation in polluted water and wastewater. r.